2010
DOI: 10.1107/s1600536810037682
|View full text |Cite
|
Sign up to set email alerts
|

catena-Poly[[silver(I)-μ-4-aminopyridine] perchlorate]: a 1-D staircase coordination polymer

Abstract: Reaction of 4-amino­pyridine with silver(I) perchlorate leads to a one-dimensional coordination polymer, {[Ag(C5H6N2)]ClO4}n, in which the amino­pyridine binds through both N atoms. The perchlorate anion is hydrogen bonded to the amino H atoms and inter­acts weakly with the silver(I) atoms (Ag—O > 2.70 Å), both located on inversion centres, and some aromatic H atoms (O—H > 2.55 ÅA), thereby extending the dimensionality of the assembly. This is the first silver complex in which this ligand acts in a bridging mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…40,41 There are several reports of hydrogen bonded networks based on [Ag(4-AP) 2 ]. 35,[42][43][44][45][46][47] These include both lamellar and three-dimensional examples. A notable difference between the homoconjugated dimers and the silver complexes is that the pyridine rings in the silver complexes are often nearly coplanar.…”
Section: Comparisons With Topologies Of Related Compoundsmentioning
confidence: 99%
“…40,41 There are several reports of hydrogen bonded networks based on [Ag(4-AP) 2 ]. 35,[42][43][44][45][46][47] These include both lamellar and three-dimensional examples. A notable difference between the homoconjugated dimers and the silver complexes is that the pyridine rings in the silver complexes are often nearly coplanar.…”
Section: Comparisons With Topologies Of Related Compoundsmentioning
confidence: 99%
“…For other silver complexes with the same ligand, see: Bowmaker et al (2005); Drew et al (2005); Di Nicola et al (2010). For examples of our previous work on silver complexes, see: Steel (2005); Fitchett & Steel (2006); O'Keefe & Steel (2007); Steel & Fitchett (2008); Golder et al (2010). For details of the coordination geometry of four-coordinate silver, see: Young & Hanton (2008).…”
Section: Related Literaturementioning
confidence: 99%
“…For some time we have been involved in the study of silver complexes of chelating and bridging heterocyclic ligands (Steel, 2005;Fitchett & Steel, 2006;O′Keefe & Steel, 2007;Steel & Fitchett, 2008;Golder et al, 2010). 2-acetylpyridine coordinates to a variety of transition metals, usually as an N,O-chelating ligand, although it has been reported to act as an O-monodentate donor to a zinc porphyrin (Byrn et al, 1993).…”
Section: S1 Commentmentioning
confidence: 99%
“…Complexes with 2-,3-or 4-NH2py ligands show that NH2py tends to act as a monodentate ligand by binding to the central atom via the N pyridine ring. Complexes that have been reported such as [Ni(NCS)2(2-NH2py)2.C4H10O] [7], {∞[Cd(µ-SCN)2(4-NH2py)2]} [8], [Cu(SCN)2(x-NH2py)2] (x=2,3, or 4) [4], and [M(3-NH2py)2(dca)2] (M=Mn2+, Cu2+,Cd2+, or Co2+; dca = dicyanamide) [1,[9][10][11], [AgL(x-NH2py)2] [12][13][14][15][16] demonstrated the formation of polymer complexes via bridge formation by bidentate ligands such as dicyanamide, thiocyanate and azide. Several other complexes with monodentate ligands such as Cl¬ such as…”
Section: Introductionmentioning
confidence: 99%
“…The development of silver(I) complex compounds with pyridine and its derivatives has become an interesting topic because their structures allow them to form monomers, dimers and even polymers, as well as their biological activity which are quite extensive. Silver complexes with 2,3 and 4 aminopyridines have been reported to form complexes with various geometries such as, linear [12,13,16,21], trigonal geometry [15,21,22], square-planar geometry [23], tetrahedral [24] and etc. In general, the aminopyridines are bonded to central ions through the N atoms of the pyridine ring, but Golder et al, 2010 showed the formation of 1-dimensional polymers through 4aminopyridine bridge ligand in their complex.…”
Section: Introductionmentioning
confidence: 99%